PENGARUH FEAR OF MISSING OUT (FOMO) DAN PEER CONFORMITY TERHADAP PURCHASE INTENTION IPHONE DI KOTA BANJARMASIN - Siti Salma Kamila; M. Hasanur Arifin; Taharuddin; Saladin Ghalib (Smart Business Journal (SBJ), 2025)
This study aims to determine how the influence of Fear of Missing Out (FOMO) and Peer Conformity on iPhone Purchase Intention in Banjarmasin City. This study also describes the level of FOMO, social conformity, and consumer purchase intention for iPhone products. In addition, this study tests partially and simultaneously the effect of FOMO and Peer Conformity on Purchase Intention. The research location is in Banjarmasin City with a total of 100 respondents selected using non-probability sampling with purposive sampling method. Data collection was carried out using a questionnaire, and data analysis techniques using multiple linear regression tests. The results of this study prove that Fear of Missing Out has a positive but insignificant effect on iPhone Purchase Intention in Banjarmasin City. Peer Conformity has a positive and significant effect on iPhone Purchase Intention in Banjarmasin City. And Fear of Missing Out and Peer Conformity have a positive and significant effect on iPhone Purchase Intention in Banjarmasin City.